The teacher facilitator of the second decade of the 21st century: Reflections on Carl Rogers’ humanist theory (Research, Society and Development, 2024)
This article aims to reflect on the role of the humanist theory of the facilitator teacher structured by the North American psychologist Carl Rogers. In the discussions, we sought to understand the teacher as a singular being and, at the same time, a plural being, within the scope of a new professionalism that he lives and develops in contemporary times between the last years of the 20th century and the beginning of the 21st century. For analysis and discussion, qualitative bibliographic research was carried out by authors that debate the humanist theory and bring concepts to the Rogerian approach to the teacher facilitator concept: Mizukami, Rossi, and Moreira. The humanist conception of education was based on Puente, Zimring, Goulart, Castaman, and Tommasini. Throughout the text, the conceptual understanding of Carl Rogers permeated the analyses. In the reflection, some aspects of Rogers’ perspective on education were discussed. The results highlighted the three basic elements for building an efficient, empathetic, and authentic relationship between teacher and student to achieve meaningful learning based on the Rogerian triad.